Evaluation of the Heat Produced by the Hydrothermal Liquefaction of Wet Food Processing Residues and Model Compounds - Morgane Briand; Geert Haarlemmer; Anne Roubaud; Pascal Fongarland (ChemEngineering, 2022)
Hydrothermal liquefaction has proven itself as a promising pathway to the valorisation of low-value wet food residues. The chemistry is complex and many questions remain about the underlying mechanism of the transformation. Little is known about the heat of reaction, or even the thermal effects, of the hydrothermal liquefaction of real biomass and its constituents. This paper explores different methods to evaluate the heat released during the liquefaction of blackcurrant pomace and brewers’ spent grains. Some model compounds have also been evaluated, such as lignin, cellulose and glutamic acid. Exothermic behaviour was observed for blackcurrant pomace and brewers’ spent grains. Results obtained in a continuous reactor are similar to those obtained in a batch reactor. The heat release has been estimated between 1 MJ/kg and 3 MJ/kg for blackcurrant pomace and brewers’ spent grains, respectively. Liquefaction of cellulose and glucose also exhibit exothermic behaviour, while the transformation of lignin and glutamic acid present a slightly endothermic behaviour.